2016
DOI: 10.4236/oje.2016.67043
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Silver Nanoparticles with Neomycin or Gentamicin Antibiotics on Mastitis-Causing <i>Staphylococcus aureus</i>

Abstract: Objective: Mastitis is one of the most costly diseases in dairy cows, which greatly decreases milk production. Use of antibiotics in cattle leads to antibiotic-resistance of mastitis-causing bacteria. The present study aimed to investigate synergistic effect of silver nanoparticles (AgNPs) with neomycin or gentamicin antibiotic on mastitis-causing Staphylococcus aureus. Materials and Methods: In this study, 46 samples of milk were taken from the cows with clinical and subclinical mastitis during the august-Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…The results obtained from this study are consistent with that of other researches. Indeed, gentamycin plus Ag-NPs in several studies demonstrated enhanced or even synergistic antibacterial effect against (Barapatre, et al 2016;Chhibber, et al 2017;Ebrahimi, et al 2017;Jamaran and Zarif 2016;Katva, et al 2017;Mohamed, et al 2017;Panacek, et al 2015;Satapathy, et al 2017;Verma, et al 2017;Wang, et al 2016).Moreover, in a good agreement with reported data in the literature, penicillin (Ebrahimi, et al 2017;Panacek, et al 2015) in contrary to some studies (Deng, et al 2016;Natan and Banin 2017;Wang, et al 2016) and ciprofloxacin in the case of human strains (Mohamed, et al 2017;Yallappa, et al 2015) in accord with our data (Panacek, et al 2015) showed significant increase in antibacterial activities when conjugated with Ag-NPs. Furthermore, tetracycline (Deng, et al 2016;Ebrahimi, et al 2017;Natan and Banin 2017), amoxicillin (Mohamed, et al 2017), cephalosporin (Refat, et al 2017), erythromycin (Yallappa, et al 2015 showed partially increase in antibacterial activities in the presence of Ag-NPs.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained from this study are consistent with that of other researches. Indeed, gentamycin plus Ag-NPs in several studies demonstrated enhanced or even synergistic antibacterial effect against (Barapatre, et al 2016;Chhibber, et al 2017;Ebrahimi, et al 2017;Jamaran and Zarif 2016;Katva, et al 2017;Mohamed, et al 2017;Panacek, et al 2015;Satapathy, et al 2017;Verma, et al 2017;Wang, et al 2016).Moreover, in a good agreement with reported data in the literature, penicillin (Ebrahimi, et al 2017;Panacek, et al 2015) in contrary to some studies (Deng, et al 2016;Natan and Banin 2017;Wang, et al 2016) and ciprofloxacin in the case of human strains (Mohamed, et al 2017;Yallappa, et al 2015) in accord with our data (Panacek, et al 2015) showed significant increase in antibacterial activities when conjugated with Ag-NPs. Furthermore, tetracycline (Deng, et al 2016;Ebrahimi, et al 2017;Natan and Banin 2017), amoxicillin (Mohamed, et al 2017), cephalosporin (Refat, et al 2017), erythromycin (Yallappa, et al 2015 showed partially increase in antibacterial activities in the presence of Ag-NPs.…”
Section: Discussionsupporting
confidence: 92%
“…Gentamicin and neomycin are hydrophilic however silver nanoparticles are hydrophobic. For this reason, silver nanoparticle in contrast to antibiotics can easily bypass cellular membrane and reach to the target cell effectively [134].…”
Section: Review Of Some Neomycin Nanoparticle Formulationsmentioning
confidence: 99%
“…Throughout the previous years, much anxiety has been raised regarding the treatment failure. Consequently, continual attention has given by the researchers to discover new strategies for treatment (Dehkordi et al, 2011;Jamaran & Zarif, 2016). Recently, nano drugs have been used as a substitute measure to solve the multi-drug resistance and intracellular persistence of S. aureus which associated with the subclinical and relapsing infection of bovine mastitis (Le Ray et al, 2005;Franci et al, 2015;Wang et al, 2017;…”
Section: Introductionmentioning
confidence: 99%